Dramaturgical Analysis of Vlogger’s Impression Management on Social Media - Ester Krisnawati (Komunikator, 2020)
The presence of social media is not only used by someone to communicate with other people but also to present oneself with certain goals. The appearance of celebgram and vloggers has shown that social media is a place to show oneself in front of others. This study aims to describe the impression management vlogger in the "Kumit Project" account on social media by using a dramaturgy approach. The observation units in this study were the Kumit Project’s accounts on Instagram and Youtube. This qualitative descriptive study used the Erving Goffman dramaturgical analysis approach. The results showed that when on the front stage, Kumit Project, through its actors Madkucil and Cimit, performed impression management to create an impression on their audience. While on the back stage, Kumit Project was a team with the actors Madkucil and Cimit, whom the relationship as lovers was portrayed as the front stage. The drama that they played on the front stage is a real picture like the one on the back with additional background settings to add to the dramatization.